2017
DOI: 10.1007/s00216-017-0776-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an easy-to-use method for the routine analysis of the central metabolism using an affordable low-resolution GC–MS system: application to Arthrospira platensis

Abstract: We developed an easy-to-use method for the routine analysis of the central metabolism using an affordable low-resolution GC-MS system run in SIM mode. The profiling approach was optimized for the derivatization protocol of some 60 targeted metabolites. The performance of two silylation reagents (MSTFA and BSTFA) that allowed the comprehensive derivatization of 42 key intermediary metabolites of the 60 initially targeted (organic acids, phosphate derivatives, monosaccharides and amino acids) was measured. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The repeatability and reproducibility were considered acceptable and in line with the values commonly found for plant metabolomics (ca. 25-35%) [27]. All the results indicated that tobacco pseudotargeted GC-MS analysis is a dependable approach for metabolic profiling.…”
Section: Metabolite Identification and Methods Evaluationmentioning
confidence: 90%
“…The repeatability and reproducibility were considered acceptable and in line with the values commonly found for plant metabolomics (ca. 25-35%) [27]. All the results indicated that tobacco pseudotargeted GC-MS analysis is a dependable approach for metabolic profiling.…”
Section: Metabolite Identification and Methods Evaluationmentioning
confidence: 90%